(untitled) (Journal of Pakistan Orthopaedic Association, 2023)
A young female presented with swelling and pain in right knee joint with difficulty in functions for 9 months. There was a firm to hard and tender swelling of 10cmx8cm around the anterior and medial aspect of the right knee joint not separable from the patella. After radiological imaging and incisional biopsy, non-malignant giant cell tumor was diagnosed. We performed total patellectomy with complete resection of patellofemoral contents including quadricep tendon and inferior margins of muscles without any extensor reconstruction. Patient was walking without support after 6 weeks without any brace. X-rays showed periarticular osteopenia. After 2-years, she presented with pathological right supracondylar femur fracture that was managed with DFLCP and denosumab. GCT of patella with massive soft tissue extension can be managed with patellectomy and wide resection without extensor reconstruction. Periarticular osteopenia needs to be managed to avoid pathological fractures by giving denosumab.